Efficient artificial fish swarm based clustering approach on mobility aware energy‐efficient for MANET - Gupta, Deepak; Khanna, Ashish; SK, Lakshmanaprabu; Shankar, K.; Furtado, Vasco; Rodrigues, Joel J. P. C. (Transactions on emerging telecommunications technologies, 2019)
Mobile ad hoc network (MANET) is a gathering of self‐ruling mobile nodes in which ad hoc network framed without settled foundation. Dynamic topology property of MANET may debase the execution of the network, mobility attentiveness, and energy effectiveness because of an ideal cluster head (CH). The low energy adaptive clustering hierarchy protocol is used in the MANETs for enhancement of network life time by proficiently utilizing of the accessible constrained energy. Artificial fish swarm optimization is used to select the CH in MANET communication process. The election of CH takes care of mobility and remaining energy as well as the degree of connectivity for selecting nodes to serve as cluster for longer duration of time. From the implementation results, it is observed that the proposed method provides the maximum network life time as 80 to 140 hours and minimum energy consumption as 9 to 130 J, compared with existing protocol and optimization technique. Model for proposed work. AFS, artificial fish swarm; CH, cluster head; LEACH, low energy adaptive clustering hierarchy. The LEACH protocol is used in the MANETs for enhancement of network lifetime by proficiently utilizing of the accessible constrained energy. Artificial Fish Swarm (AFS) optimization is used to select the CH in MANET communication process. The election of CH takes care of mobility and remaining energy as well as the degree of connectivity for selecting nodes to serve as a cluster for the longer duration of time. The energy consumption of the suggested routing protocol is very low comparing to the existing energy routing protocols.